(untitled) (Journal of The Colloquium for Information Systems Security Education, 2020)
The importance of incorporating cybersecurity education in K-12 to develop and strengthen the pipeline of students who pursue a cybersecurity major in college along with teaching cyber-awareness to all students cannot be overstated. Through efforts, such as the National Institute of Science and Technology (NIST) National Initiative for Cybersecurity Education (NICE) K-12 cybersecurity conferences and the NICE K-12 working groups this message is being spread to K-12 educators across the country. In Virginia, like many other states, there is a disparity among student and teacher preparation in cybersecurity between urban and rural areas. Schools lack two key resources: teachers with the required competencies and access to isolated computing networks – required for hands on exercises in security. Currently, efforts to introduce security are usually focused only at the high school level where students have already self-selected into relatively small interest groups. This paper describes the result of year-long, NSA funded project (PICSAR) designed to increase the number of teachers with competency in cybersecurity, while increasing the pipeline of students interested in cybersecurity. The project accomplished the first goal by providing graduate instruction in cybersecurity education and workshops to K-12 teachers. These same teachers then helped to accomplish the second goal through the development of age appropriate, integrated, STEAM lesson plans from Kindergarten through the 12th grade. For each topic in cybersecurity (e.g. Cryptography), a skills progression plan was developed and then lesson plans developed and piloted to appropriately introduce the topic at each grade level.